Odnos između sposobnosti fonemske diskriminacije i artikulacije kohlearno implantirane dece predškolskog uzrasta - Bjelić, Marija; Isaković, Ljubica; Veletić, Marija; Kordić, Milena (Specijalna edukacija i rehabilitacija, 2024)
Introduction. The acquisition of the native language is achieved through mastering the phonological system, which relies on the development of phonemic discrimination and articulation. Objectives. The aim of this study was to examine the relationship between phonemic discrimination and articulation during the period of intensive speech language development in preschool children with hearing impairment. Methods. The study involved 20 children with cochlear implants aged between 36 and 77 months. The development of phonemic discrimination and articulation was assessed using the Phoneme Discrimination Test and the Global Articulation Test. Results. The results of the study indicate that children who better distinguish phonemes have statistically significantly better results on the Global Articulation Test, and that there is an interrelation between phonemic discrimination and articulation in the participants. The results also show better achievements in phonemic discrimination and articulation in the group of children who participated in auditory training daily, compared to children who participated in auditory training twice a week. Chronological age, auditory age, and the duration of auditory training were not statistically significantly related to the participants’ articulation and phonological abilities. Conclusion. Analysis of the study results concludes that the ability to discriminate phonemes and articulation in preschool children with cochlear implants are interrelated. Chronological age, auditory age, and the duration of auditory training were not found to be indicators associated with the participants’ articulation and phonological abilities. The frequency of auditory training is the only identified factor related to phonemic discrimination and articulation abilities in preschoolers with cochlear implants.